Economic evaluation approaches for new technology. - Papatheofanis, F.J.
The thrust of development supporting new medical devices and agents for the treatment of disease rightfully remains focused on the scientific and clinical underpinnings that justify the use of such new products and the replacement of others. Many devices and agents are introduced in the United States each year, and diagnostic and therapeutic regimens (standards of care) are often adapted to integrate new technology. When and how to use new devices and compounds can be problematic to clinicians, and it is difficult for payers (insurance companies and the federal government) to assess these new technologies for the purpose of coverage and reimbursement. For example, many chemotherapeutic compounds are effective as single agents but become even more effective when used in combination with other agents. In the most dramatic example, the development of new biologicals and immunotherapies continues at a brisk pace; these agents often display intricate chemical characteristics and represent the practical results of combinatorial and other advanced methodologies for synthesizing, and screening candidate molecules. Payers will have to make coverage decisions on these and other emerging technologies using methods involving health economics and health technology assessment. The economic valuation of new technology is an important tool for those making coverage and policy decisions. Here we explore some of the characteristics of economic valuations and their use.
Keywords: United States; Candidate molecules screening; Chemotherapeutic compounds; Combinatorial methodologies; Diagnostic regimens; Economic evaluation approaches; Federal government; Immunotherapies; Insurance companies; Intricate chemical characteristics; Policy decisions; Reimbursement; Therapeutic regimens